Brand and packaging design for adding value of instant red jasmine rice porridge - Jaimun, Ratchadaporn; Uprarawanna, Utsaphong; Kanha, Nattapong (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
The objectives of this study are to design the brand and package of instant red jasmine rice porridge for the organic agricultural community enterprise promotion group in U Thong district, Suphan Buri province and to study of satisfaction toward the brand and packaging prototype. After brainstorming, three styles of brand and four styles of package were designed by the graphics software. Afterwards, the satisfactions in all of the designed styles were evaluated on 234 consumers, 15 entrepreneurs and 15 brand and packaging design specialists using a self-administrative questionnaire. The accidental sampling technique was used for consumers while purposive sampling was applied for entrepreneurs and specialists. The results showed that all groups of the evaluators scored the highest overall satisfaction especially for its identity for the Style 2 which symbolized by a picture of a farmer who is holding a sickle with a symbol of number nine in Thai style as an inspiration. This implied the story of farmers who have been planted and processed rice products by themselves in every steps. For packaging, all evaluator groups scored the highest overall satisfaction for the Style 2, followed by Style 3 and 1, respectively. Style 2 is created by emphasizing on simplicity. In addition, an image of the product stands out by using pastel colors. Therefore, Style 2 got the highest score due to its color and art composition.